Deep venous thrombosis among disaster shelter inhabitants following the March 2011 earthquake and tsunami in Japan: a descriptive study. (May 2014) - Shibata, M; Hanzawa, K; Ueda, S; Yambe, T
Objectives: A retrospective analysis of data collected during subject screening following Japan's March 2011 earthquake and tsunami was performed. We aimed to determine the incidence of deep venous thrombosis (DVT) among screened subjects and to identify risk factors associated with the development of DVT as independent variables. Methods: Calf ultrasonography was undertaken in 269 subjects living in 21 shelters in Miyagi prefecture during the one-month period immediately following the March 2011 disaster. Information regarding the health and risk factors of subjects was collected by questionnaire and assessment of physical signs. Results: Of the 269 evacuees screened, 65 (24%) met the criteria for calf DVT. We found lower limb trauma, reduced frequency of urination and sleeping in a vehicle to be independent positive predictors of DVT. Conclusions: Evacuees had an increased risk of developing DVT, associated with tsunami-related lower limb injury, immobility and dehydration.